MRI findings in the lumbar spines of asymptomatic, adolescent, elite tennis players. Issue 11 (19th July 2007) - Alyas, F; Turner, M; Connell, D
Abstract : Objective: To describe magnetic resonance imaging (MRI) findings in the lumbar spine in asymptomatic elite adolescent tennis players, to serve as the baseline for a future prospective longitudinal cohort study. Design: Observational study. Setting: Institutional, national tennis centre. Participants: 33 asymptomatic elite adolescent tennis players, mean (SD) age, 17.3 (1.7) years (18 male, 15 female). Methods: Sagittal T1, T2, STIR, and axial T2 weighted MRI images were reviewed for the presence of abnormalities by two radiologists in consensus. Abnormalities included disc degeneration, disc herniation, pars lesions (fracture or stress reaction), and facet joint arthropathy. Results: Five players (15.2%) had a normal MRI examination and 28 (84.8%) had an abnormal examination. Nine players showed pars lesions (10 lesions; one at two levels) predominately at the L5 level (9/10, L5; 1/10, L4). Three of the 10 lesions were complete fractures; two showed grade 1 and one grade 2 spondylolisthesis, both of which resulted in moderate narrowing of the L5 exit foramen. There were two acute and five chronic stress reactions of the pars. Twenty three patients showed signs of early facet arthropathy occurring at L5/S1 (15/29 joints) and L4/5 (12/29 joints). These were classified as mild degeneration (20/29) and moderate degeneration (9/29), with 20/29 showing sclerosis and 24/29 showing hypertrophy of the facet joint. Synovial cysts were identified in 14 of the 29 joints. Thirteen players showed disc desiccation and disc bulging (mild in 13; moderate in two) most often at L4/5 and L5/S1 levels (12 of 15 discs). Conclusions: Abnormalities were frequent, predominately in the lower lumbar spine, almost exclusively at L4/5 and L5/S1 levels. Pars injuries and facet joint arthroses were relatively common.